Prevalence of resistant hypertension and associated factors for blood pressure control status using Korean ambulatory blood pressure monitoring registry data. Issue 1 (December 2016) - Choi, Sung; Kim, Soon; Park, Sungha; Kim, Ju; Ihm, Sang; Kim, Gwang-il; Kim, Woo; Pyun, Wook; Kim, Yu-Mi; Shin, Jinho
Abstract Background Resistant hypertension (RH) may be one of the cause of the plateau in improving the control rate in hypertension (HT) management. The misdiagnosis of RH by clinic blood pressure (BP) is important clinical problem. Aim of the study were to investigate the prevalence of RH by ambulatory blood pressure monitoring (ABPM) and the factor associated with control status of ambulatory BPs. Methods For 1230 subjects taking one or more antihypertensive medication (AHM) enrolled in the Korean Ambulatory Blood Pressure Monitoring (Kor-ABP) registry, the prevalence of RH was calculated which was defined as uncontrolled BP by three AHM classes including diuretic or BP in need of four or more AHM classes. The prevalence determined by clinic versus ambulatory BP was compared. Results The age was 59.3 ± 12.5 years, and 44.3 % were female (n = 1230). Among them 72 subjects were taking three AHM drugs including diuretics and 105 subjects were taking four or more AHM classes. With uncontrolled daytime ambulatory BP in 41 among 72 subjects, prevalence of RH was 11.9 % (146/1230). By using nighttime BP criteria, there was significant difference in the prevalence of RH for clinic versus nighttime BP (146/177 vs. 159/177, p = 0.0124). For control status of daytime BP, masked uncontrolled BP was 16.9 % and controlled BP with white-coat effect was 14.1 %. For nighttime BP control status, odd ratios for smoking (0.624), drinking (1.512), coronary artery disease (0.604), calcium antagonist (1.705), and loop diuretics (0.454) were all significant. Conclusion The prevalence of RH was 11.9 % by daytime BP and it was significantly higher when using nighttime BP criteria. Control status of daytime BP was misclassified in 31.0 %. Smoking, drinking, coronary artery disease, calcium antagonist, and loop diuretics were associated with nighttime BP control status.